DAMPAK PENAMBANGAN EMAS ILEGAL DI KABUPATEN BURU TERHADAP KONSENTRASI MERKURI (Hg) PADA KEPITING BAKAU (Scylla serrata) DAN KEONG BAKAU (Telescopium telescopium) - Irsan, Irsan; Koto, Saifuddin; Ismail, Irwan; Dahlan, Rosmida R; Mangesa, Rosita (Program Studi Pendidikan Biologi FKIP Unpatti, 2023)
Background: Illegal gold mining in Buru Regency uses the heavy metal mercury toprocess gold material, so it can pollute the environment, including aquatic biota such asmangrove crabs (Scylla serrata) and mangrove snails (Telescopium telescopium). The aimof this research is to analyze the amount of mercury concentration and the level of pollutionin mangrove crabs and snails as a result of illegal gold mining in Buru Regency.Methods: Research samples were taken at the Waelata River Estuary and the AnahoniRiver Estuary. For mercury analysis, 8 mangrove crabs and 16 mangrove snails weretaken. Analysis of mercury concentration using the AAS Cold Vapor method.Results: The results showed that the heavy metal mercury was detected in mangrovecrabs and mangrove snails. The concentration of mercury detected is still below the qualitystandard set based on heavy metal contamination (SNI) No. 7387 of 2009, specifically forthe heavy metal Hg in shellfish (bilvalves), mollusks and sea cucumbers, shrimp and othercrustaceans at 1.0 mg/kg (ppm).Conclusion: Illegal gold mining in Buru Regency has an impact on mercury concentrationsin mangrove crabs and mangrove snails, but the value is still below the specified qualitystandards. However, consumption of mangrove crabs and mangrove snails that live aroundgold mining areas in Buru Regency must be limited, considering the nature of mercuryaccumulation.